STRUKTUR RUPA TOPENG BALI KLASIK - I Wayan Suardana (Imaji, 2006)
This study of classical Balinese masks aims at discovering and introducing the local and traditional Balinese values with a hope that the result might become input for mask development in Indonesia. The focus of the study is the mask forms, especially those related to symbols in religious belief. The data were collected from references, informants chosen proportionally through purposive sampling and notes from historic sources as well as direct field notes. The result shows that based on structure and form there is similarity between classical Balinese masks and puppets. The similarity can be seen from their dots, lines, shapes, colors, and textures. The form elements reached the peak since the fall of Majapahit. The art traditions of East Java that had gone through synthesis were continued in Bali and accumulated with the local culture. The process enriched the existing arts, producing pajegan, panca, and bobondreasan masks. The masks are used as educational media applied in Hindu religious teachings and philosophy. The characters are taken from Mahabaratha and Ramayana epics. Keywords: visual structure, classical Balinese masks